(untitled) (Stamford Journal of Microbiology, 2016)
Present study attempted to emphasize on the drug-resistance attribute of the previously isolated microorganisms within the commonly available flowers including Hibiscus rosa-sinensis, Ixora coccinea, Ipomoea digitata, Allamanda cathartica, Nymphaea nouchali, Vinca rosea, Rosa kordesii, Gladiolus hybrid, Acmella oleracea, Nyctanthes arbor-tristis and Pseudomussaenda flava, randomly collected from different areas in Dhaka city, Bangladesh. Conventional agar well diffusion method was applied to examine the antibiogram of the isolates (Escherichia coli, Klebsiella spp., Pseudomonas spp., and Staphylococcus spp.) against different drugs. Subsequently the anti-bacterial traits of 6 flowers such as Rosa kordesii, Gladiolus hybrid, Acmella oleracea, Nymphaea nouchali (Water lily), Hibiscus rosa- sinensis (Jaba), Ixora coccinea (Rangan) were demonstrated through broth micro-dilution methods. Pseudomonas spp. showed sensitivity against almost 42% tested drugs. Conversely, Staphylococcus spp. (83%) and Klebsiella spp. (75%) revealed resistance against highest number of drugs. Among all the pathogens, E coli showed the highest sensitivity (50%) against all the tested antibiotics. All the isolated bacteria were found to be multi-drug resistant against commonly used antibiotics. Finally six (6) samples unveiled anti-bacterial features against 8 laboratory strains with their MIC concentrations up to 0.2 mg/mL. Stamford Journal of Microbiology, Vol.5(1) 2015: 5-8